The Use of the (Cynodon Dactylon) Plant Waste for the Removal of Nickel and Cadmium from Aqueous Solutions by Adsorption (Texas Journal of Agriculture and Biological Sciences, 2022)
This study was carried out to find a new, affordable, and ubiquitous adsorbent that has the ability to remove trace metals. In this study, Cynodon dactylon dried grass was used. The proposed adsorbent shows a faster and higher removal for Cadmium (Cd) than it was for Nickel (Ni). The removal efficiency (R%) was decreased from 78 to52% and from 32 to 13 % for Cd and Ni respectively as the initial metal concentrations increased from 10 to 50 ppm. while the R% increased from 52 to 63% and from 13 to 17% for Cd and Ni respectively as the adsorbent weight increased from 0.25 to 0.5 gm and after that it reach equilibrium. On the other hand, Cd removal was the highest in acidic conditions while Ni removal was highest in alkaline conditions. Throughout the whole study, the proposed adsorbent shows a much higher ability to remove Cd than it was for Ni.